CONVERSION, ORDINATION, BREAKERS - Aquino, Julio Groppa (Sala Preta, 2014)
This paper aims to offer a brief reflection on the scenic route of the spectacle Pulsão. Electing Caio Fernando Abreu and Michel Foucault as interlocutors, it proposes a narrative journey backed by three asymmetric but complementary argumentative moves. The aim is thus to explore the hypothesis that the inexorable task of theatrical practices is franking shelter and flow to the power of life, which even in the limit duel with death can constitute itself as a source of unsuspected strength and creation.